PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH BRAND IMAGE PADA MAHASISWA/I DI KOTA CIMAHI SEBAGAI KONSUMEN RICHEESE FACTORY - Amelia, Riri Risa; Faizal Fardhani Sigarlaki (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of electronic word of mouth on purchase intention mediated by brand image on students in Cimahi City as consumers of Richeese Factory. The type of research used in this study is quantitative with descriptive analysis. The population taken is students in Cimahi City with a sample of 150 respondents taken using the method of purposive sampling. The data analysis technique used is a simple and double regression test using version 26 and using a compact test. The results of the study showed that electronic word of mouth had a positive and significant influence on the brand image with a thitung value of 8,108 > 1,655215 and a significance value of 0,000 < 0,05. Electronic Word of Mouth has a positive and significant impact on the purchase intention with a value of 7,368 and a signifying value of 0,000 < 0,055. Brand image has a positive influence and a significant effect on the purchasing intention of 2,856 and the significance of 0,005 < 0.05. Brand image plays a role in mediating the influence of electronic word of mouth on purchase intention with a thitung value of 2,701 and a significance value of 0,006 < 0,05.